The geology of the 2nd century A.D. Amphitheater Area of Catania, Italy: Historical Eruptions Affecting the Urban District. Issue 1 (20th October 2015) - Branca, Stefano; Branciforti, Maria Grazia; Chiavetta, Antonio Fernando; Corsaro, Rosa Anna
Abstract : The amphitheater of Catania is one of the main architectural structures built during Roman domination of the town. It was constructed in two successive phases between the 1st and 2nd centuries A.D. and fell into disuse from the second half of the 4th century. Detailed geological and petrographic investigations allow better geomorphological reconstruction of the area where the monument was built. In particular, the western and eastern portions of the amphitheater are built on prehistoric lava flows, named Barriera del Bosco and Larmisi, respectively. We infer that the choice of site to build the monument was highly influenced by the morphological setting of the area. In fact, the location at the contact between two lava flow fields facilitated excavation and removal of rocks due to the incoherence of the scoriaceous lateral border of the lava flows. Integrating both archaeological and geological data has revealed that a large number of Neolithic, Greek, and Roman sites are located in the lava fields of Barriera del Bosco and Larmisi within the present urban district of Catania, indicating that during its long history the city was directly impacted by only one lava flow, namely in A.D. 1669.